2013
DOI: 10.1038/bjc.2013.764
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic silencing of miRNA-9 is associated with HES1 oncogenic activity and poor prognosis of medulloblastoma

Abstract: Background:microRNA-9 is a key regulator of neuronal development aberrantly expressed in brain malignancies, including medulloblastoma. The mechanisms by which microRNA-9 contributes to medulloblastoma pathogenesis remain unclear, and factors that regulate this process have not been delineated.Methods:Expression and methylation status of microRNA-9 in medulloblastoma cell lines and primary samples were analysed. The association of microRNA-9 expression with medulloblastoma patients' clinical outcome was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 73 publications
3
33
0
Order By: Relevance
“…Our recent findings further demonstrated that the human R antigen post-transcriptionally regulates the expression of miR-7 (17). In addition, recent evidence indicated that histone methylation or CpG methylation may affect the expression of distinct miRNA molecules in certain types of cancers (27,28). Therefore, the predominant mechanism involved in the repressed expression of the miR-7 gene remains to be fully elucidated in future studies.…”
Section: Promoter Mutation Is Associated With Repressed Expression Ofsupporting
confidence: 52%
“…Our recent findings further demonstrated that the human R antigen post-transcriptionally regulates the expression of miR-7 (17). In addition, recent evidence indicated that histone methylation or CpG methylation may affect the expression of distinct miRNA molecules in certain types of cancers (27,28). Therefore, the predominant mechanism involved in the repressed expression of the miR-7 gene remains to be fully elucidated in future studies.…”
Section: Promoter Mutation Is Associated With Repressed Expression Ofsupporting
confidence: 52%
“…Both the identification and functional characterization of distinct miRNAs in human MB have been extensively reported . Likewise, the role of miRNA in CSCs has been described in several tumors .…”
Section: Discussionmentioning
confidence: 99%
“…The specific miRNA expression signatures in brain tumours have received great attention in the last few years and can facilitate the diagnosis and prediction of the therapy response and prognosis [10]. It has been reported that the expression of some miRNAs is associated with survival in medulloblastoma patients [11,13,14]. …”
Section: Introductionmentioning
confidence: 99%